Treatment with a BH3 mimetic overcomes the resistance of latency III EBV (+) cells to p53-mediated apoptosis. - HOLLVILLE, EMILIE (Nature, 2011)
P53 inactivation is often observed in Burkitt's lymphoma (BL) cells due to mutations in the p53 gene or overexpression of its negative regulator, murine double minute-2 (MDM2). This event is now considered an essential part of the oncogenic process. Epstein-Barr virus (EBV) is strongly associated with BL and is a cofactor in its development. We previously showed that nutlin-3, an antagonist of MDM2, activates the p53 pathway in BL cell lines harboring wild-type p53. However, nutlin-3 strongly induced apoptosis in EBV (-) or latency I EBV (+) cells, whereas latency III EBV (+) cells were much more resistant. We show here that this resistance to apoptosis is also observed in latency III EBV (+) lymphoblastoid cell lines. We also show that, in latency III EBV (+) cells, B-cell lymphona 2 (Bcl-2) is selectively overproduced and interacts with Bcl-2-associated X protein (Bax), preventing its activation. The treatment of these cells with the Bcl-2-homology domain 3 mimetic ABT-737 disrupts Bax/Bcl-2 interaction and allows Bax activation by nutlin-3. Furthermore, treatment with these two compounds strongly induces apoptosis. Thus, a combination of Mdm2 and Bcl-2 inhibitors might be a useful anti-cancer strategy for diseases linked to EBV infection.
PUBLISHED
Keywords: Genetics; Oncology; Burkitt's lymphoma